2018
DOI: 10.1097/hjh.0000000000001599
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial factors in the pathogenesis and treatment of chronic kidney disease Part I

Abstract: : Kidney damage is a common consequence of arterial hypertension, but is also a cause of atherogenesis. Dysfunction and/or harm of the endothelium in glomeruli and tubular interstitium damage the function of these structures and translates into dynamic changes of filtration fraction, with progressive reduction in glomerular filtration rate, expansion of extracellular fluid volume, abnormal ion balance, and hypoxia, ultimately leading to chronic kidney disease. Considering the key role played by endothelial dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…CKD is one of the top public health problems and leading diseases for all-cause mortality globally (Xie et al, 2018). The putative mechanisms regarding the pathogenesis and progression of CKD have been well documented previously (Fogo, 2007; Malyszko, 2010; Eddy et al, 2012; Yang et al, 2017; Cheung et al, 2018; Mihai et al, 2018; Moradi and Vaziri, 2018; Rossi et al, 2018). Briefly, both generic factor-caused genital abnormality of renal development, and other factors (e.g., inflammation, hypertension, diabetes, dyslipidemia, disorder of cytokines and growth factors, proteinuria, podocyte loss, etc.)…”
Section: Preclinical Studies Of the Treatment Of Renal Dysfunction Bymentioning
confidence: 77%
“…CKD is one of the top public health problems and leading diseases for all-cause mortality globally (Xie et al, 2018). The putative mechanisms regarding the pathogenesis and progression of CKD have been well documented previously (Fogo, 2007; Malyszko, 2010; Eddy et al, 2012; Yang et al, 2017; Cheung et al, 2018; Mihai et al, 2018; Moradi and Vaziri, 2018; Rossi et al, 2018). Briefly, both generic factor-caused genital abnormality of renal development, and other factors (e.g., inflammation, hypertension, diabetes, dyslipidemia, disorder of cytokines and growth factors, proteinuria, podocyte loss, etc.)…”
Section: Preclinical Studies Of the Treatment Of Renal Dysfunction Bymentioning
confidence: 77%
“…Furthermore, observational studies associate sleep duration with markers of endothelial dysfunction 43 . Thus, given that derangements in the renin-angiotensin-aldosterone system and endothelial dysfunction 44 are well-established mechanisms underlying kidney damage, studies should examine their potential role in the observed association between sleep and CKD to determine the nature of this relation.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological role of the ET system in the kidney (Figure 3) appears to be dominated by the high expression of ET B Rs primarily, but not exclusively, located in the principal cells within the inner medullary collecting duct (reviewed in [28][29][30] ). In fact, high-salt diets are powerful stimulators of ET-1 production within the kidney tubule and even nonrenal sources of ET-1.…”
Section: Renal Pathophysiological Effects Of Et-1mentioning
confidence: 99%